Les investissements dans l'environnement des acteurs des circuits courts de proximité agroalimentaires - Sophie Rétif; Marius Chevallier (VertigO)
This article studies short food supply chains (SFSC) and analyzes the way participants in these SFSC invest in environmental values and representations. For this purpose, we use the concept of environmental capital. Our analysis is mainly based upon 40 interviews with various participants in the SFSC in the Limousin region (agricultural producers, consumers, intermediaries, local government actors, etc.) and twenty analytical forms of collective SFSC organizations. We use these interviews and forms to understand the importance that is given to environmental issues in the development of SFSC. Although the organic products are over-represented among the agricultural products commercialized through SFSC, the environmental issues are rarely mentioned in the interviews, as are health issues. The agricultural producers and the consumers hardly talk about environmental issues. Yet, if SFSC participants do not frequently speak about the environment, some signs show that these participants have some environment-related expectations. We thus analyze these signs and the conditions of their production. We also demonstrate that the valorisation of the environmental dimension of the SFSC depend on social, cultural and economic capitals.